Climatic change and debris flows in high mountain regions: The case study of the Ritigraben torrent (Swiss Alps) - Rebetez, M.; Lugon, R.; Baeriswyl, P. A. (2006)
Debris flows in the region of Ritigraben (Valais, Swiss Alps), which generally occur in the months of August and September, have been analyzed in relation to meteorological and climatic factors. The principal trigger mechanisms for such debris flows are abundant rain on the one hand, and snow-melt and runoff on the other hand, or a combination of both. Debris flows linked to rain are likely to be triggered when total rainfall amount over a three-day period exceeds four standard deviations, i.e., a significant extreme precipitation event. An analysis of climatological data for the last three decades in the region of Ritigraben has highlighted the fact that the number of extreme rainfall events capable of triggering debris flows in August and September has increased. Similar trends are observed for the 20th Century in all regions of Switzerland. The general rise in temperature in a region of permafrost may also play a role in the response of slope stability to extreme precipitation. At the foot of the Ritigraben, warming trends of both minimum and maximum temperatures have been particularly marked in the last two decades.